ANTERIOR PELVIC PLATE OSTEOSYNTHESIS AND PERCUTANEOUS SACROILIAC JOINT SCREW FIXATION IN OPEN-BOOK PELVIS FRACTURE - Badaruddin Sahito1, Jagdesh Kumar2, Nusrat Rasheed3, Muhammad Soughat Katto4, Dileep kumar5, Asif Ali Jatoi6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
INTRODUCTION: Osteofixation using the Plate-Screw system is currently regarded as the gold standard for open-book pelvic fractures; it provides stable fixation and also permitting early mobilization and rehabilitation. OBJECTIVE: To determine the outcome of anterior plate osteosynthesis and percutaneous sacroiliac screw fixation for open-book pelvic fracture. METHODOLOGY: This retrospective and cross-sectional study was performed at the Department of Orthopaedic, Dr KM Pfau Civil Hospital, Karachi, Pakistan from January 2017 to December 2019. In this study, we reviewed the medical record of all skeletally mature patients who underwent surgical treatment for open-book pelvis fracture (Tile B and Young-Burgess APC II). Patients with open fracture, or associated with acetabular fractures, concomitant spinal injuries, and those definitively managed with external pelvic fixator were excluded. The functional outcome was evaluated according to Majeed scoring system. Immediate postoperative and follow-up radiographs at minimum 6-month were reviewed for evidence of screw loosening and implant failure. RESULTS: A total of 19 patients; 4(21.1%) females and 15(78.9) males with a mean age of 38.47 ± 10 years were included. Five patients (26.3%) underwent combined anterior plate fixation and posterior sacroiliac (SI) joint screw fixation. 14 patients (73.7%) underwent only anterior symphyseal plate fixation. Trauma due to road traffic accidents was the most frequent cause and was observed in 13 (68.4%) cases. Partial screws back-out was noted in 1 patient. According to Majeed functional scoring system averaged 77.94 (50–96); 04(21.1%) patients achieved excellent while 11(57.9%) patients had good outcome. 03 (15.7%) patients showed a fair outcome while 1 (5.3%) had poor functional outcome. CONCLUSION: We concluded that anterior plating and a supplemental posterior fixation is a safe and effective method for the stabilization of anterior pelvic ring fracture. It produces a low rate of complication and provides stable fixation to enable early mobilization.